2018
DOI: 10.1111/cts.12549
|View full text |Cite
|
Sign up to set email alerts
|

Novel Application of the Two‐Period Microtracer Approach to Determine Absolute Oral Bioavailability and Fraction Absorbed of Ertugliflozin

Abstract: Ertugliflozin, a sodium glucose cotransporter‐2 inhibitor, is approved in the United States for treatment of type 2 diabetes mellitus. A novel two‐period study design with 14C microtracer dosing in each period was used to determine absolute oral bioavailability (F) and fraction absorbed (Fa) of ertugliflozin. Eight healthy adult men received 100‐μg i.v. 14C‐ertugliflozin (400 nCi) dose 1 h after a 15‐mg oral unlabeled ertugliflozin dose (period 1), followed by 100 μg 14C‐ertugliflozin orally along with 15 mg o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
63
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 32 publications
(66 citation statements)
references
References 16 publications
3
63
0
Order By: Relevance
“…6 Ertugliflozin AUC inf and C max values following 15-mg dosing in the current study of Chinese subjects are comparable with those in Western subjects (AUC inf : 1113-1636 ng·h/mL; C max : 169-319 ng/mL, in Western subjects) after receiving the same single doses of 15 mg of ertugliflozin. 15,[17][18][19][20][21] A pooled analysis of the current study of Chinese subjects together with 16 other phase 1 studies conducted in healthy subjects showed geometric means of dose normalized AUC inf and C max after single-dose administration in Chinese subjects are 1.20-and 1.34fold of those in non-Asian subjects, respectively (data on file). Similarly, following multiple-dose administration of ertugliflozin under fed conditions in 3 studies, geometric mean of dose normalized AUC tau and C max in Chinese subjects are 1.33-and 1.50-fold of those in non-Asian subjects, respectively.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…6 Ertugliflozin AUC inf and C max values following 15-mg dosing in the current study of Chinese subjects are comparable with those in Western subjects (AUC inf : 1113-1636 ng·h/mL; C max : 169-319 ng/mL, in Western subjects) after receiving the same single doses of 15 mg of ertugliflozin. 15,[17][18][19][20][21] A pooled analysis of the current study of Chinese subjects together with 16 other phase 1 studies conducted in healthy subjects showed geometric means of dose normalized AUC inf and C max after single-dose administration in Chinese subjects are 1.20-and 1.34fold of those in non-Asian subjects, respectively (data on file). Similarly, following multiple-dose administration of ertugliflozin under fed conditions in 3 studies, geometric mean of dose normalized AUC tau and C max in Chinese subjects are 1.33-and 1.50-fold of those in non-Asian subjects, respectively.…”
Section: Discussionmentioning
confidence: 70%
“…19 The terminal elimination half-life (t ½ ) of ertugliflozin ranges from 11 to 17 hours. 5,6,[15][16][17][18][19][20][21][22] The PK of ertugliflozin are similar in healthy subjects and in patients with T2DM. 20 The major clearance pathway of ertugliflozin is metabolism via glucuronidation (86%) with minor contribution from oxidative metabolism (12%).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Absolute bioavailability of ertugliflozin is ∼100% . The terminal‐phase half‐life (t ½ ) is in the range of 11 to 17 hours .…”
mentioning
confidence: 99%
“…6 The area under the plasma concentration-time curve (AUC) for ertugliflozin increases in a dose-proportional manner over the dose range of 0.5 to 300 mg. 7 Absolute bioavailability of ertugliflozin is ß100%. 8 The terminal-phase half-life (t ½ ) is in the range of 11 to 17 hours. 7 After oral administration of a radioactive ertugliflozin dose, excretion of radioactivity in urine and feces accounted for 50.2% and 40.9% of the dose, respectively.…”
mentioning
confidence: 99%